Evaluation of mixed microalgae Chlorella vulgaris and tetradesmus bernardii for cultivation and nutrient removal in palm oil mill effluent - Wais, Mohammad Navid; Zulkifly, Shahrizim; Ibrahim, Mohd Hafiz; Mohamed, Afiqah; Zana Rudin, Zana Ruhaizat (Universiti Putra Malaysia, 2024)
The palm oil industry is one of the key players in contributing to Malaysia’s economy. Palm oil mill effluent (POME), a significant by-product of the oil extraction process, requires mandatory remediation to ensure proper treatment and disposal. Bioremediation using microalgae is a cost-effective and sustainable approach. This study aims to utilise pure and mixed microalgal species, Chlorella vulgaris and Tetradesmus bernardii, in phycoremediation and biomass production in different concentrations of POME (20%, 40%, 60%, and 80%). Cultivation of microalgae was carried out in 200 mL medium with pH 7–7.8, room temperature of 25±1°C for 21 days and continuous light illumination at 2000 lux. The highest biomass productivity was observed in 20% POME for mixed microalgae (mean = 0.1733 mg.mL-1 ± 0.0057), followed by C. vulgaris (0.1633 mg.mL-1 ± 0.0057) and T. bernardii (0.1603 mg.mL-1 ± 0.0020). Similarly, the highest nutrient removal was observed in 20% POME for mixed microalgae (COD:66.9801%, TN:86.9565%, TP:86.9655%), followed by C. vulgaris and T. bernardii. The results showed positive effects on growth, increased biomass production, and nutrient removal, with 20% POME being the optimal concentration for microalgae. Valuable by-products, such as high-quality pigments and biomass, are also generated by applying microalgae for remediation. Mixed microalgae are superior in the remediation of POME compared to single-culture algae. Treating wastewater through microalgal bioremediation is highly efficient in nutrient removal. This research has contributed towards the use of mixed microalgae to achieve effective nutrient removal and biomass for future industrial applications.